Pengetahuan dan Sikap Tentang Tanda Bahaya Dalam Kehamilan Serta Keaktifan Ibu Dalam Kelas Ibu Hamil - Nurfatimah Nurfatimah; Lisa Fiarsi; Lisda Widianti Longgupa; Kadar Ramadhan (Jurnal Sehat Mandiri, 2020)
The implementation of pregnancy class in the Puskesmas Mapane in Poso Regency is still ineffective because it is done every three months. The purpose of this study to find out knowledge and attitudes about danger signs in pregnancy and the activeness of mothers in classes of pregnant women in the working area of Puskesmas Mapane in Poso Regency. Research methods using cross-sectional design. The population in this study were second-trimester and third-trimester pregnant women in the working area of Puskesmas Mapane, 96 mothers. The sample in this study were 77 people who determined by simple random sampling. Chi square test is used to analyze the relationship between knowledge and attitudes with maternal activity in pregnant mother classes.The resultsshowed that from 77 people, there were 84.4% pregnant women who were not active in pregnancy class and pregnant women who had good knowledge and positive attitudes about the danger signs of pregnancy as many as 73.9%. The conclusion is that the activeness of the mother in the class of pregnant women is not very influential in increasing the mother's knowledge about the danger signs of pregnancy. Suggestions are expected to the Puskesmas so that they can better provide information and motivation to pregnant women to take pregnancy class programs in their working areas.